Nonlinear Dynamics of a Thin Plate in a Nonstationary Electromagnetic Field of the Inductor - Morachkovsky, Oleg K.; Lavinsky, D. V. (Изд-во "Точка", 2013)
The problems of the non-stationary deformation of a thin round plates in the electromagnetic field (EM-field) created by a massive inductor are considered. The finite element method is used for the analysis of spatial-temporal distribution of the electromagnetic field components and the parameters of the stress-strain state in the system of the «inductor-billet (plate)» with a consideration of the air layer. The data of measurements in experimental studies of vibrations of plates in pulsed EM-field are used to establish the frequency modes with the maximum values ponderomotive forces generated by an EM-field. The solution of the problem of plate vibrations was obtained. The temporal and spatial distribution of components of the electromagnetic field, displacements and stresses on the surface of the plate with the analytical solutions and experimental data are compared. Areas with the maximum displacements and stresses in the plate were installed for some «configuration» of electromagnetic field
Keywords: vibrations; deforming